2020
DOI: 10.18502/kss.v4i12.7592
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetic of Cuteness Dimensions in Malang City Mascot

Abstract: Osi and Ji are Malang City mascots made with coherent design procedures. They represent a particular identity to appeal to the target audience. This paper examines the aesthetics of cuteness that synergize between the dimensions of affection, language, and design in the city’s mascot. The study is based on qualitative research with observations and interviews conducted between April and September 2018. The affective dimension of Osi and Ji is linked with their anthropomorphism. It creates a high level of intim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In support, Schnurr (2019) revealed that whimsically cute packaging design significantly influences consumer purchase intention; the effectiveness of cute design has been proven to influence consumer response and behavior (e.g. Gn, 2016;Steinnes et al, 2019;Novica et al, 2020). Thus, we hypothesize that, MIP 41,5…”
Section: Can Packaging Overcome Product Unfamiliarity?mentioning
confidence: 81%
See 3 more Smart Citations
“…In support, Schnurr (2019) revealed that whimsically cute packaging design significantly influences consumer purchase intention; the effectiveness of cute design has been proven to influence consumer response and behavior (e.g. Gn, 2016;Steinnes et al, 2019;Novica et al, 2020). Thus, we hypothesize that, MIP 41,5…”
Section: Can Packaging Overcome Product Unfamiliarity?mentioning
confidence: 81%
“…While past studies have explored cute features individually, such as colors (e.g. Cheok, 2010;Komatsu and Ohkura, 2011;Gong et al, 2017), characters (Dydynski and M€ aekivi, 2018;Schnurr, 2019;Novica et al, 2020), logos (e.g. Septianto and Paramita, 2021), shapes (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations